Machine Learning in Computational Surface Science and Catalysis: Case Studies on Water and Metal–Oxide Interfaces - Li, Xiaoke; Paier, Wolfgang; Paier, Joachim (Frontiers in Chemistry, 2020)
The goal of many computational physicists and chemists is the ability to bridge the gap between atomistic length scales of about a few multiples of an Ångström, i.e. 10-10 m, and meso- or macroscopic length scales by virtue of simulations. The same applies to time scales. Machine learning techniques appear to bring this goal into reach. This work applies the recently published on-the-fly machine-learned force field techniques using a variant of the Gaussian approximation potentials (GAP) combined with Bayesian regression and molecular dynamics as efficiently implemented in the Vienna ab initio simulation package, VASP. The generation of these force fields follows active-learning schemes. We apply these force fields to simple oxides like MgO and more complex reducible oxides like iron oxide, examine their generalizability and further increase complexity by studying water adsorption on these metal oxide surfaces. We successfully examined surface properties of pristine and reconstructed MgO and Fe3O4 surfaces. However, the accurate description of water-oxide interfaces by machine learned force fields, especially for iron oxides, remains a field offering plenty of research opportunities.